8-Gingerol Ameliorates Myocardial Fibrosis by Attenuating Reactive Oxygen Species, Apoptosis, and Autophagy via the PI3K/Akt/mTOR Signaling Pathway - Xue, Yucong; Zhang, Muqing; Liu, Miaomiao; Liu, Yu; Li, Li; Han, Xue; Sun, Zhenqing; Chu, Li (Frontiers in Pharmacology, 2021)
8-gingerol (8-Gin) is the series of phenolic substance that is extracted from ginger. Although many studies have revealed that 8-Gin has multiple pharmacological properties, the possible underlying mechanisms of 8-Gin against myocardial fibrosis (MF) remains unclear. The study examined the exact role and potential mechanisms of 8-Gin against isoproterenol (ISO)-induced MF. Male mice were intraperitoneally injected with 8-Gin (10 and 20 mg/kg/d) and concurrently subcutaneously injected with ISO (10 mg/kg/d) for 2 weeks. Electrocardiography, pathological heart morphology, myocardial enzymes, reactive oxygen species (ROS) generation, degree of apoptosis, and autophagy pathway-related proteins were measured. Our study observed 8-Gin significantly reduced J-point elevation and heart rate. Besides, 8-Gin caused a marked decrease in cardiac weight index and left ventricle weight index, serum levels of creatine kinase and lactate dehydrogenase (CK and LDH, respectively), ROS generation, and attenuated ISO-induced pathological heart damage. Moreover, treatment with 8-Gin resulted in a marked decrease in the levels of collagen types I and III and TGF-β in the heart tissue. Our results showed 8-Gin exposure significantly suppressed ISO-induced autophagosome formation. 8-Gin also could lead to down-regulation of the activities of matrix metalloproteinases-9 (MMP-9), Caspase-9, and Bax protein, up-regulation of the activity of Bcl-2 protein, and alleviation of cardiomyocyte apoptosis. Furthermore, 8-Gin produced an obvious increase in the expressions of the PI3K/Akt/mTOR signaling pathway-related proteins. Our data showed that 8-Gin exerted cardioprotective effects on ISO-induced MF, which possibly occurred in connection with inhibition of ROS generation, apoptosis, and autophagy via modulation of the PI3K/Akt/mTOR signaling pathway.